Articulando características do sistema de numeração decimal para o ensino de números - Weslei Lima de Figueiredo (2019)
This work emerges from experiences and reflections about the teaching of numbers in elementary school. It assumes that a better understanding of the Decimal Numeral System core characteristics, such as factorization, may favor both teaching and learning of positive rational numbers in decimal form.This study also assumes the possibility of acting in the face of persistent challenges in the development of operative capacities with decimal numbers in primary school. The Decimal Numeral System, here addressed as "DNS", is widely used in modern societies and, its applications, already indispensable for an uncountable number of situations, are accessible to all. The richness and potentiality of DNS shows itself even greater when we combine the teaching of natural numbers with decimal numbers, emphasizing how comprehensive the DNS really is. We then point out the need for improvement on the perception of the DNS's features to understand the algorithms behind the operations, highlighting the factorization and defactorization of numbers, the various meanings of positional value, the arrangement of rational numbers alongside natural numbers, etc. We present a set of explanatory and exploratory activities, where we look for DNS elements to better understand numbers and operations on the multiplication and division operations in varied situations. Our work turns to a dialogue with the teachers, aiming at both starter and in-service teacher training, considering to expand teaching possibilities and offer elements to face difficulties.